Evaluation Of English For Business ESP Textbooks: Content Analysis Approach - Abdul Syahid; Syahrul Mubaroq; Muhammad Noor Fauzan; Adinda Aulia Rahmah; Noor Muthi’ah (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
This research evaluates an English for Business textbook written by Mary Ellen Guffey & Carolyn M. Seefer with a content analysis approach. This study focuses on exploring the structure, content, and learning features in textbooks to assess their suitability to learner needs and stated goals. The examination conducted to assess the textbooks in this research employed a qualitative descriptive approach using the Cunningsworth and Miekley checklist as its foundation. The assessment scale encompasses ratings ranging from 'very good' and 'good' to 'moderate' and 'poor'. The analysis revealed the textbook's effectiveness in facilitating learning through its structured layout, engaging examples, and interactive features. Additionally, contextualization in real business scenarios and sections that promote discussion increase its relevance and applicability. This study offers valuable insights for educators, curriculum developers, and policy makers in selecting and developing ESP textbooks tailored to the specific needs of learners in the business field.